Exploring the implementation of the school-based mental health program for adolescents in Indonesia: A mixed-methods study - Kusumawardani, Riastuti; Chun Paek, Seung; Ratanawijitrasin, Sauwakon; Phukao, Darunee (Public Health of Indonesia, 2023)
Background: Mental health issues among adolescents have become a public concern in Indonesia. The Indonesian government introduced the School-Based Mental Health (SBMH) program in 2017 and has implemented it in all public junior high schools in Jakarta. However, there is a relative scarcity of evidence regarding how schools have implemented the SBMH. Objective: This study aimed to explore the SBMH program and its implementation in public junior high schools. Methods: Mixed methods were employed in 12 public junior high schools (6 from East Jakarta and 6 from West Jakarta) using a purposive sampling method from May 6 to August 30, 2021. Descriptive statistics and content analysis were applied to the data analysis. Results: The main inhibiting factor for the implementation of the SBMH program was the school curriculum. Schools that received the Health School Award had more trained teachers to facilitate the SBMH program compared to schools without the award. Consequently, schools with the award successfully implemented regular mental health education in the classroom, screening, and counseling for students with mental health issues more effectively than schools without the award. Conclusion: The government should gradually strengthen resources to facilitate the SBMH program in the long term. In the short and medium term, the government should develop a collaboration network by supporting external mental health providers, professionals, and counselors.